Impact of single annual treatment and four-monthly treatment for hookworm and Ascaris lumbricoides, and factors associated with residual infection among Kenyan school children. Issue 1 (December 2017) - Kepha, Stella; Mwandawiro, Charles; Anderson, Roy; Pullan, Rachel; Nuwaha, Fred; Cano, Jorge; Njenga, Sammy; Odiere, Maurice; Allen, Elizabeth; Brooker, Simon; Nikolay, Birgit
Abstract Background School-based deworming is widely implemented in various countries to reduce the burden of soil-transmitted helminths (STHs), however, the frequency of drug administration varies in different settings. In this study, we compared the impact of a single annual treatment and 4-monthly treatment over a follow-up among Kenyan school children, and investigated the factors associated with residual infection. Methods We performed a secondary analysis of data from a randomized trial investigating whether deworming for STHs alters risk of acquiring malaria. Children received either a single treatment or 4-monthly albendazole treatments were followed longitudinally from February 2014 to October 2014. The relative impact of treatment and factors associated with residual infections were investigated using mixed-effects regression models. Predisposition to infection was assessed based on Spearman's rank and Kendall's Tau correlation coefficients. Results In the 4-monthly treatment group, the proportion of children infected with hookworm decreased from 59.9 to 5.7%, whileAscaris lumbricoides infections dropped from 55.7 to 6.2%. In the single treatment group, hookworm infections decreased over the same time period from 58.7 to 18.3% (12.6% absolute difference in reduction, 95%CI : 8.9–16.3%), andA. lumbricoides from 56.7 to 23.3% (17.1% absolute difference in reduction, 95%CI : 13.1–21.1%). There was strong evidence for predisposition to both STH types. Residual hookworm infection among children on 4-monthly treatment were associated with male sex and baseline nutritional status, whereasA. lumbricoides infection was associated with individual and school-level infection at baseline, latrine cleanliness at schools. Conclusions This study found that 4-monthly treatment w more effective than single annual treatment. Repeated treatments led to dramatic reductions in the intensities of STHs, but did not completely clear infections among school children in Kenya, a presumed reflection of reinfection in a setting where there is ongoing transmission.